Capturing Essentials in Wound Photography Past, Present, and Future: A Proposed Algorithm for Standardization. (September 2022) - Onuh, Ogechukwu C.; Brydges, Hilliard T.; Nasr, Hani; Savage, Elizabeth; Gorenstein, Scott; Chiu, Ernest
Abstract : GENERAL PURPOSE: To discuss a standardized methodology for wound photography with a focus on aiding clinicians in capturing high-fidelity images. TARGET AUDIENCE: This continuing education activity is intended for physicians, physician assistants, nurse practitioners, and nurses with an interest in skin and wound care. LEARNING OBJECTIVES/OUTCOMES: After participating in this educational activity, the participant will be able to: 1. Discriminate the components of high-quality wound photography. 2. Identify the technological innovations that can augment clinical decision-making capacity. 3. Choose strategies that can help clinicians avoid adverse medicolegal outcomes. ABSTRACT: Significance: According to a 2018 study, chronic wounds affect more than 8 million Americans and impose a substantial economic burden, with costs of care reaching upward of US 30 billion. As demographics in the US shift toward an aging population, these numbers are likely to progressively increase annually. Care of these patients relies heavily on photographic documentation, which catalogs disease progression and informs management decisions. This article elaborates a standardized methodology for wound photography and aims to aid clinicians in capturing high-fidelity images. Recent Advances: Technological advancements, notably digital cameras and smart phones, have exponentially improved both the rate and quality of wound photography, but their potential has yet to be fully realized. Critical Issues: Despite the indispensable nature of wound photography, literature detailing the photography process remains sparse. The absence of a standardized methodology for wound photography leads to subpar documentation, which ultimately hinders patient care. Further, information regarding medicolegal implications of wound photography remains fragmented and opaque to many clinicians. The authors provide a comprehensive overview of best practices in wound photography, medicolegal considerations, and an overview of emerging technologies. Future Directions: Photographic documentation is indispensable in the management of chronic wounds. Capturing consistent, high-fidelity images requires the adoption of standardized protocols. Emerging technologies, such as three-dimensional imagery, biosensors, and artificial intelligence, are poised to profoundly alter wound photography in the future. However, standardized protocols informed by sound clinical judgment will remain of paramount importance.